1981
DOI: 10.1177/014616728174008
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Shyness on Loneliness in a New Situation

Abstract: Subjects completed a trait-measure of shyness and a state-measure of loneliness at the start of a new semester (Time 1), and repeated the loneliness measure at the end of the semester (Time 2). Shy students had significantly higher loneliness scores than unshy students at Time 1. Both groups showed a decline in loneliness over the length of the semester, presumably due to habituation, but the shy students were still significantly lonelier than the unshy students at the end of the semester. These findings indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
4

Year Published

1984
1984
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(66 citation statements)
references
References 3 publications
4
58
0
4
Order By: Relevance
“…Shy individuals and observers alike usually describe shy behaviors as reticent, quiet, awkward, or overactive (Cheek & Briggs, 1982;Zimbardo, 1982). Shy college students are less visible and less assertive in the workplace, and are less likely to use career-planning resources (Cheek & Busch, 1981). They display less verbal fluency and fewer leadership skills.…”
Section: Behaviormentioning
confidence: 99%
“…Shy individuals and observers alike usually describe shy behaviors as reticent, quiet, awkward, or overactive (Cheek & Briggs, 1982;Zimbardo, 1982). Shy college students are less visible and less assertive in the workplace, and are less likely to use career-planning resources (Cheek & Busch, 1981). They display less verbal fluency and fewer leadership skills.…”
Section: Behaviormentioning
confidence: 99%
“…Studies have found that loneliness is positively associated with shyness (Cheek and Busch, 1981), communication apprehension (Zakahi and Duran, 1985), and social anxiety (Segrin and Kinney, 1995). Many studies further provided evidence indicating that skill deficits precede loneliness.…”
Section: Loneliness and Poor Social Skillsmentioning
confidence: 99%
“…Furthermore, Cheek and Buss (1981) demonstrated that shyness and sociability are orthogonal, suggesting that being shy does not necessarily equate to desiring less social contact. Finally, compared to the less shy, shy individuals report being lonelier (Cheek & Busch, 1981;Neto, 1992) and less socially satisfied (Jones & Carpenter, 1986), indicating unmet social desires.…”
Section: Theories Of Shynessmentioning
confidence: 99%